The relationship between areas of life satisfaction, personality, and overall life satisfaction: An integrated account - Malvaso, Antonio; Kang, Weixi (Frontiers in Psychology, 2022)
A substantial amount of research has been conducted using a variety of methodological approaches to determine what influences life satisfaction. Bottom-up theory considers overall life satisfaction as a function of various areas of life satisfaction. The top-down theory considers the areas of life satisfaction as a function of personality. We examined these models in a large-scale UK survey. Consistent with other studies, we found that both bottom-up and top-down models of life satisfaction are supported in a different cultural context (i.e., UK) by demonstrating that both personality traits and life satisfaction variables can explain a significant portion of variance in overall life satisfaction. We propose that future study in life satisfaction research should consider the integrated account of life satisfaction rather than a unitary bottom-up or top-down perspective.